2011
DOI: 10.1007/s13105-011-0116-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of curcumin, α-lipoic acid, and N-acetylcysteine against carbon tetrachloride-induced liver fibrosis in rats

Abstract: Liver fibrosis is a major health problem that can lead to the development of liver cirrhosis and hepatocellular carcinoma. On the other hand, several antioxidants have been shown to possess protective effect against liver fibrosis. Therefore, in the present work, the effectiveness of curcumin, α-lipoic acid, and N-acetylcysteine in protecting against carbon tetrachloride (CCl(4))-induced liver fibrosis as well as the mechanism(s) implicated in this protective effect was studied. The antioxidants used in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 23 publications
7
38
0
Order By: Relevance
“…5), aggregations of inflammatory cells and marked inflammatory changes associated with fatty changes (Fig.6), focal necrotic areas, congestion and pyknotic nuclei were also observed (Fig.7). These observations agree with Manjrekar, Jisa, Bag, and Adikary (2008); Morsy et al (2012); Morakinyo, Oludare, Anifowose, and Adegoke (2012); Domitrovic et al (2015);and Hismiogullari et al (2015). Masson trichrome stained sections showed congested thickened portal tract with dense fibrous tissues radiating from the portal vein and extending into the parenchyma (Fig.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…5), aggregations of inflammatory cells and marked inflammatory changes associated with fatty changes (Fig.6), focal necrotic areas, congestion and pyknotic nuclei were also observed (Fig.7). These observations agree with Manjrekar, Jisa, Bag, and Adikary (2008); Morsy et al (2012); Morakinyo, Oludare, Anifowose, and Adegoke (2012); Domitrovic et al (2015);and Hismiogullari et al (2015). Masson trichrome stained sections showed congested thickened portal tract with dense fibrous tissues radiating from the portal vein and extending into the parenchyma (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Also, Wang et al (2014 reported that NAC was able to ameliorate oxidative stress and cytotoxicity in HepG cells. Additionally, Morsy, Abd Alla, Mahmoud, Abdel Wahab, and Mahmoud (2012) showed that curcumin, α-lipoic acid and NAC caused a significant decrease of hepatic MDA levels as compared to CCL4 fibrotic rats. However, results revealed insignificant change in serum total protein in all groups as compared to control; this was context with Hanafi (2012).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In these models, curcumin showed a major role as an inhibitor of HSC activation; it also seems to be able to reduce liver damage, as well as the a-SMA and procollagen expression in the liver, when administered in CCl 4 -induced liver fibrosis models for 4-8 weeks. The recognized mechanism of action in those models included curcumin's ability to target multiple sites, such as platelet-derived growth factor-b receptor (PDGF-bR) [37], matrix metalloproteinases (MMPs) [37,38], tissue growth factor b (TGFb) [39,40], peroxisome proliferator-activated receptors (PPARc) [41], toll-like receptors (TLRs) [42], apoptotic pathway [43,44], inflammatory cytokines [41,42,45,46] and microRNAs [47,48]. Recently, curcumin's capacity to increase cyclic adenosine monophosphate levels, which leads to an increase in the number of mitochondrial DNA duplicates, has been demonstrated [49].…”
Section: Inflammation and Fibrosismentioning
confidence: 99%
“…When this balance is broken by hyperactivation of HSCs, fibrosis occurs. Available evidence showed that curcumin plays a role in downregulation of TIMP-1 and TIMP-2 in vivo [38,[71][72][73] and in vitro [74], while it upregulates MMP-2 [73], MMP-7 [72], MMP-9 [73] and MMP-13 [38,72]. This leads to inhibition of HSC activation due to the degradation of one of the main components of the ECM, the fibrillar collagens.…”
Section: Inflammation and Fibrosismentioning
confidence: 99%